Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702252
|View full text |Cite
|
Sign up to set email alerts
|

Improving Accuracy, Applicability and Usability of Keystroke Biometrics on Mobile Touchscreen Devices

Abstract: Authentication methods can be improved by considering implicit, individual behavioural cues. In particular, verifying users based on typing behaviour has been widely studied with physical keyboards. On mobile touchscreens, the same concepts have been applied with little adaptations so far. This paper presents the first reported study on mobile keystroke biometrics which compares touch-specific features between three different hand postures and evaluation schemes. Based on 20.160 password entries from a study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 51 publications
(104 reference statements)
1
73
0
Order By: Relevance
“…Most of the evaluation methods in the literature are based on verification mode such as in [29,8,24], some other little evaluation methods have been used based on identification mode such as in [30]. Table 2 compares different proposed active authentication methods based on keystroke dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the evaluation methods in the literature are based on verification mode such as in [29,8,24], some other little evaluation methods have been used based on identification mode such as in [30]. Table 2 compares different proposed active authentication methods based on keystroke dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 compares different proposed active authentication methods based on keystroke dynamics. Buschek et al [8] evaluated their proposed authentication mechanism on a private dataset with 20160 samples. They used different models to make verification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments using characters as well as PIN have been conducted. Starting with EER 6.9% of the study using 6 characters [9], experiment using 6 to 8 characters showed EER of 21.02% [15], using 10 characters showed EER of 0.806% [16], and using 34 characters showed EER of 9.3% [17], respectively. Later, there was a new type of study that extracts pressure and time interval from image instead of keys [6].…”
Section: Related Workmentioning
confidence: 91%
“…This approach could be easily combined with any text-input authentication methods as a typing pattern is unique for each person [119][120][121]. In case the MFA system is specifically developed for predefined gesture analysis [122], the user is required to replicate a previously learned movement while holding or wearing the sensing device [123][124][125].…”
Section: Behavior Detectionmentioning
confidence: 99%